Two cases of Clostridium difficile infection in unrelated oncology patients attributable to a single clone of C. difficile PCR ribotype 126. Issue 3 (June 2015) - Knight, Daniel R; Hart, Julie; Gottardo, Nicholas G; Eyre, David W; Crook, Derrick W; Riley, Thomas V
Abstract : Introduction: Clostridium difficile is a significant gastrointestinal pathogen and a leading cause of life-threatening diarrhoea in the developed world. Antibiotic therapy and immunodeficiency are key risk factors for C. difficile infection (CDI); consequently, oncology patients are at high risk. Case presentation: We present two cases of CDI in unrelated oncology patients from different Western Australian hospitals in 2012. The first, a 59-year-old male, presented with diarrhoea 3 weeks after admission to hospital for treatment of a grade IV glioblastoma. Symptoms commenced after receiving prophylactic perioperative cephazolin. The second case was a 2-year-old female who presented with several episodes of diarrhoea after extended hospitalization following treatment for a stage 4 neuroblastoma. The patient had been exposed to regimens of piperacillin/tazobactam and ciprofloxacin for febrile neutropaenia and intra-abdominal sepsis. In both cases, the diarrhoea resolved after commencement of oral metronidazole. Both patients had an uncommon strain of C. difficile (PCR ribotype 126) detected in stool specimens, and both strains belonged to an unusual multilocus sequence type (ST), ST258. Comparison of the genomes of both strains by whole-genome sequencing showed them to be indistinguishable (no single-nucleotide variants). No epidemiological link between the patients was identified. Conclusion: These data suggest that both cases resulted from exposure to a common source, most likely food contaminated with livestock faeces. Moreover, this is the first report of ribotype 126 isolates belonging to a ST (ST258) other than ST11. Our cases highlight the need for continued molecular surveillance of C. difficile, and the genetic analysis of emerging ribotypes.